Surgical Interventions for the Management and Treatment of Chronic Migraine in Clinical Nursing Practice - Essa, Maha Ali; Fayez Sumayhan Hirab alharbi; Soad Hassan Fardos Ghanem; Anaam Hassan Hashem Alshakes; Hind Yahya Hassan Huraysi; Najla abdullah barzig; Aliah Abdullah Mohammed barzig; Rawia Hassan Maghfouri; Hamad Mohaimeed Hamad Alotaibi; Abdulmajeed Obaid Abdullah Alotaibi; Hayam Hammoud Safhi; Amal Abdullah Ali Majrashi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Chronic migraine is a disabling neurological disorder characterized by frequent headache episodes and significant functional impairment. While pharmacological and behavioral therapies remain first-line treatments, a subset of patients continues to experience refractory symptoms that negatively impact quality of life. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to review and synthesize current evidence on surgical and procedural interventions for the management of chronic, drug-refractory migraine, with particular emphasis on their clinical relevance within nursing and interprofessional practice. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative, evidence-based review was conducted using published clinical studies, anatomical and physiological research, and established diagnostic and therapeutic guidelines. The article examines migraine pathophysiology, indications and contraindications for surgery, and the effectiveness of interventions such as botulinum toxin injections, peripheral nerve decompression or neurectomy, rhinogenic surgery, and neuromodulation techniques. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Surgical interventions targeting peripheral nerve compression sites demonstrate meaningful reductions in migraine frequency and intensity in carefully selected patients. Botulinum toxin serves both therapeutic and diagnostic roles by identifying trigger points and predicting surgical success. Peripheral neurolysis and neurectomy show sustained benefit in refractory cases, while neuromodulation—particularly occipital nerve stimulation—offers an alternative for patients unsuitable for decompression surgery. Complication rates are generally low when procedures are appropriately indicated and performed within multidisciplinary care models. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> For patients with chronic migraine unresponsive to optimal medical therapy, targeted surgical and neuromodulatory interventions provide effective, individualized treatment options. Comprehensive evaluation, precise anatomical localization, and interprofessional collaboration are critical to achieving optimal outcomes.